Reduction of Formaldehyde Emission from Phenol Formaldehyde Treated Oil Palm Wood through Improvement of Resin Curing State - Mohamad Amarullah; Edi S. Bakar; Zaidon Ashaari; Mohd. H. Sahri; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Oil palm wood (OPW) has several imperfections, and impregnation with low molecular- weight phenol formaldehyde resin through a modified compreg method can practically enhance these properties. The treated OPW, however,  releases  a considerable  amount  of free formaldehyde and thus is unhealthy for the human being. To make it applicable  for indoor material, formaldehyde emission (FE) should  be lowered  to 0.1 ppm  or lower. The FE level of the treated OPW was reduced from 0.3 to 0.1 ppm or lower by improving the resin curing state through two approaches, i.e. modifying the hot pressing compression schedule during the process and adopting an extended drying after the process. It is acknowledged that the extended drying gave more effect on the FE reduction than that of modifying hot-pressing schedule. The combination pressing  schedule  of 12.5%®25%®50% and extended drying of 48 h emits the lowest, safe formaldehyde of 0.08-0.10 ppm, which is considered  safe  according  to  American  National  Standard Institute (ANSI) standard. The improving resin curing state through modifying the hot pressing schedule and adopting extended drying could be used as a practical  way to reduce the FE level of the treated OPW to a safe level suitable for various furniture and indoor applications.